Effect of leaf retention and flavonoids on rooting o Ilex paraguariensis cuttings - Tarrago, Jose Ramon (2005)
The effect of the mature leaf retention and the exogenous application of flavonoids (naringenin, quercetin and rutin at 30 μM for 12 h) was studied for adventitious rooting of Ilex paraguariensis cuttings. Softwood cuttings harvested from young 3-year-old plants and adult 10- and 20-year-old plants were rooted under intermittent fog. A strong correlation (r2 = 0.72) between leaf retention and rooting was noted. The highest percentage of adventitious root formation (40%) was obtained when the leaf was artificially removed after 42 days of incubation. This data was supported by the histological analysis which provided anatomical evidence that cuttings have initiated root primordia by 21 days and the regenerated roots emerge through the epidermis after 35 days of incubation. A strong correlation between the position of the leaf and the site of roots regeneration was observed. A 100% of the rooted cutting with a single leaf only formed roots along the leaf axis at the base of the cutting. Quercetin increased the rooting percentage more than three times compared to the control and all flavonoids tested improved the distribution of roots around the stem without impacting the number of regenerated roots per rooted cutting from 20-year-old plants.